Long Term Tests of Ni-YSZ|YSZ|GDC|Pr0.6Sr0.4CoO3-δ in SOFC and SOEC Regimes. (30th May 2017) - Nurk, Gunnar; Kukk, Freddy; Kanarbik, Rait; Möller, Priit; Lust, Enn
Abstract : Stability of electrochemical performance in time is one of the most important properties of SOFC/SOEC materials looking from the commercialization point of view. Alternative materials should be tested in addition to the more attractive ones for better understanding of reasons and mechanisms behind degradation processes. This work handles durability tests with 5x5 cm Ni-YSZ|YSZ|GDC|Pr0.6 Sr0.4 CoO3-δ cells in both SOFC and SOEC regimes. The SOFC performance test was conducted at 650 °C and at cell potential 0.85 V and it lasted for 17, 820 hours. Initial degradation of electrochemical performance was 2.4 % per 1000h and in the second half of the experiment, the degradation was 1.1 % per 1000h. At the end of the durability test, 18 O gas was introduced to the cell. HR-SEM and ToF-SIMS analyses were performed on the tested cells to analyze the location of 18 O, Cr, Si and Sr ions in the cell.